COMPARISON OF VARIOUS TYPES OF PIR MOTION SENSORS FOR NODEMCU ESP32 CAM IMAGE CAPTURING DEVICES - Bagye, Wire; Khairul Imtihan; Ashari , Maulana (LPPM STMIK Lombok, 2024)
Abstract:Videos and images can be used as observations or evidence of a crime. The most widely used device for recording video in an office or home is CCTV (Closed Circuit Television). The cost of installing the cheapest CCTV in Indonesia is 1,300,000 thousand Rupiah.The development of the microcontroller has been equipped with a camera module. Lilygo TTGO, NodeMCU ESP 32 CAM, Raspberry Pi, are the choices of microcontrollers with camera extensions. Using the ESP32 CAM Node MCU to record images is a cheaper option compared to using CCTV (Closed Circuit Television). The input data for the ESP32 CAM NodeMCU to detect human movement is the PIR Motion sensor module.In searches on various marketplaces, there are around 20 types of PIR Motion. Each type has a different range and delay time specifications. In this study, 6 PIR Motion sensors available on the Indonesian marketplace were tested with the types HC-SR505, HC-SR501, SR602, AM312, D203s, PIR 507. The test was carried out by assembling six PIR Motions on one PCB (Printed Circuit Board) to get data at the same time. The testing tool uses Arduino Uno by utilizing the Serial Monitor service on the Arduino IDE application. The results of the PIR sensor range test show that the HC-SR501 type has the farthest range while the HC-SR505 successfully captures images.